Dendritic Cells Are Critical for the Activation and Expansion of Vδ2+ T Cells After Allogeneic Hematopoietic Transplantation - Wang, Xiaoyu; Liu, Jiangying; Gao, Haitao; Mo, Xiao-Dong; Han, Tingting; Xu, Lan-Ping; Zhang, Xiao-Hui; Huang, Xiao-Jun (Frontiers in Immunology, 2018)
γδ T cells perform antitumor and antiviral effector functions and are involved in both innate and adaptive immunity. Vδ2+ T cells represent the predominant γδ T subset in the peripheral blood of healthy subjects. Vδ2+ T cells can be selectively activated and expanded by phosphoantigens (pAgs). Dendritic cells (DCs), as potent antigen-presenting cells, are capable of mediating pAgs–triggered Vδ2+ T cells expansion. However, the association between DCs and Vδ2+ T cell recovery in the context of hematopoietic stem cell transplantation (HSCT) remains unclear. We previously demonstrated that the recovery of Vδ2+ T cells was hampered and inversely correlated with Epstein-Barr virus (EBV) reactivation in patients undergoing haploidentical HSCT (haploHSCT). Whether Vδ2+ T cells from haploHSCT recipients can be expanded by stimulation with aminobisphosphonates or pAg–presenting DCs is of particular interest. Herein, we showed that Vδ2+ T cells recovered after haploHSCT failed to expand after ex-vivo stimulation with pamidronate. In addition, we found that the recovery of DC subsets was significantly decreased, and the concentration of myeloid DCs (mDCs) correlated significantly with Vδ2+ T cell recovery in the setting of allogeneic HSCT. Furthermore, coculture of peripheral lymphocytes from recipients with monocyte-derived and pamidronate-pretreated autologous or allogeneic DCs induced the successful expansion of Vδ2+ T cells. Of note, allogeneic DCs from third-party donors stimulated a significantly higher efficiency of Vδ2+ T cell expansion than autologous DCs. More importantly, the memory features were well retained and the cytotoxic cytokines-production capacity was significantly enhanced in the expanded Vδ2+ T cells. Taken together, these results suggest that the frequency and function of DCs are critical for the recovery of Vδ2+ T cells after allogeneic HSCT. The fact that vigorous expansions of Vδ2+ T cells were induced by phosphoantigen-pretreated DCs, especially by allogeneic third-party DCs, provides additional options for the development of individualized immunotherapy strategies that utilize the anti-viral and anti-leukemic effects of γδ T cells in the context of hematopoietic transplantation.